EXPERIMENT ON THE INFLUENCE OF POP MUSIC ON IMPROVING STUDENT CONCENTRATION - Salsabil B, Najwa; Dwi M, Rahmadhani; Rahma A, Armenia; Nabilatul F, Nabilatul F; Dwi R, Annisa; Chaerunissa, Afrida; Trinanda H, Aldhi; Mudzkiyyah, Lainatul (Jurnal Kajian Pendidikan dan Psikologi, 2025)
This study aims to explore the influence of pop music on the learning concentration of students of Walisongo State Islamic University, Semarang. Concentration is a crucial element in the learning process, often influenced by the individual's environment and habits, including listening to music. This study applied the Non-Equivalent Control Group Design experiment design with a pre-test and post-test. Of the 32 participants in this study, who were selected based on purposive sampling, students were divided into experimental groups that learned while listening to pop music and control groups without music.  The results of the analysis showed that both groups experienced an increase in average scores from pre-test to post-test, but the difference between the two groups was not statistically significant (p = 0.618) because the p value was greater than the specified significance limit (p = <0.05). These findings suggest that although pop music can create a more enjoyable learning atmosphere, its effect on study concentration is not significant. The implications of this study emphasize the importance of creating a supportive learning environment as well as providing recommendations for students to explore their personal learning preferences.